Pyramids of species richness: the determinants and distribution of species diversity across trophic levels. Issue 9 (18th April 2016) - Turney, Shaun; Buddle, Christopher M.
Abstract : How species richness is distributed across trophic levels determines several dimensions of ecosystem functioning, including herbivory, predation, and decomposition rates. We perform a meta‐analysis of 72 large published food webs to investigate their trophic diversity structure and possible endogenous, exogenous, and methodological causal variables. Consistent with classic theory, we found that published food webs can generally be described as 'pyramids of species richness'. The food webs were more predator‐poor, prey‐rich and hierarchical than is expected by chance or by the niche or cascade models. The trophic species richness distribution also depended on centrality, latitude, ecosystem‐type and methodological bias. Although trophic diversity structure is generally pyramidal, under many conditions the structure is consistently uniform or inverse‐pyramidal. Our meta‐analysis adds nuance to classic assumptions about food web structure: diversity decreases with trophic level, but not under all conditions, and the decrease may be scale‐dependent. Synthesis The distribution of species richness across trophic levels has not been evaluated in recent decades, despite improvement in food web resolution and the relevance of biodiversity distribution to ecosystem function. Our meta‐analysis of 72 large, recent food webs, illustrates that published food webs can generally be described as basal‐rich, top‐poor 'pyramids of species richness', consistent with classic theory. Although trophic diversity structure is generally pyramidal, under some environmental and ecological conditions the structure is uniform or inverse‐pyramidal. Our meta‐analysis confirms classic theory about food web structure, while adding nuance by describing conditions under which classic pyramid structure is not observed.